PRICE EARNINGS RATIO (PER) MODEL CONSISTENCY: EVIDENCE FROM JAKARTA STOCK EXCHANGE - Prof. Marwan Asri, M.B.A., Ph.D.; Antonius N. Heveadi (Gadjah Mada International Journal of Business, 1999)
Recently, stock valuation model using the earning multiplier approach (PER) is more popular among investors and analysts. This popularity has caused this model to seem to be the most perfect model among other valuation models. In response to the fact above, this research tries togive empirical evidence whether PER’s cross-sectional model can be used in determining the fairness of stock price traded in Jakarta Stock Exchange.Evaluation of the capability of PER’s cross-sectional model in determining the common stock price was conducted by developing three regression models from different time periods, namely the years of 1995, 1996, and 1997. The regression models used in this research was the one developed by Whitbeck-Kisor (1973). The model employed growth, dividend payout ratio (DPR), and standard deviation of growth (s-growth) as independent variable.This research was intended to test the consistency of the model in assessing stock prices. The result of this research showed that each model developed at different time periods, though with the same sample and method, gave different results. The differences were in the significance level and in the weight of influence of independent variables to the corresponding dependent variables. As a stock valuation model, a regression model should perform consistently from period to period, so normalPER of a stock could be predicted based on the model that was developed by historical data.